2018
DOI: 10.1063/1.5026972
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional fluid-kinetic model of a magnetically guided plasma jet

Abstract: A fluid-kinetic model of the collisionless plasma flow in a convergent-divergent magnetic nozzle is presented. The model combines the leading-order Vlasov equation and the fluid continuity and perpendicular momentum equation for magnetized electrons, and the fluid equations for cold ions, which must be solved iteratively to determine the self-consistent plasma response in a three-dimensional magnetic field.The kinetic electron solution identifies three electron populations and provides the plasma density and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
5
14
0
Order By: Relevance
“…The error in using this approximate law, in the wide parameter range considered, is found to be below 7% in the whole MN. Regarding the dependence on B, the asymptotic analysis of Ramos et al [33] for the electron population at the downstream end of the nozzle, yielded nT e u ∝ B and nT e⊥ u ∝ B 5/3 , which is confirmed here. Additionally, it is found here that similar scaling laws apply to the parallel and perpendicular heat fluxes: q e ∝ B and q e⊥ ∝ B 5/3 .…”
Section: Iv1 the Equivalent Fluid Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…The error in using this approximate law, in the wide parameter range considered, is found to be below 7% in the whole MN. Regarding the dependence on B, the asymptotic analysis of Ramos et al [33] for the electron population at the downstream end of the nozzle, yielded nT e u ∝ B and nT e⊥ u ∝ B 5/3 , which is confirmed here. Additionally, it is found here that similar scaling laws apply to the parallel and perpendicular heat fluxes: q e ∝ B and q e⊥ ∝ B 5/3 .…”
Section: Iv1 the Equivalent Fluid Modelsupporting
confidence: 84%
“…For instance, the intermediate value α = 7/2, extracted from figure 10(c), o yieldsγ ≈ 1.2, a value close to some experimental evidence [26][27][28][29]39]. Implementing the crude closure (37) in the energy equation (33) yields the known law between the electric potential fall and the polytropic coefficient, [34] e|φ…”
Section: Iv2 Electron Heat Fluxessupporting
confidence: 69%
See 1 more Smart Citation
“…Third, the electron temperature at the source is assumed isotropic, which is not the situation expected in an ECR thruster. Theoretical work is underway to cancel or at least reduce these model restrictions [34,[36][37][38] IV.2 Fitting of experimental data along the MN of the PM thruster…”
Section: Resultsmentioning
confidence: 99%
“…Subramaniam and Raja [6] have considered the simulation of axisymmetric flows of plasmas with application to spacecraft thrusters. Several simulation studies based on numerical codes such as the one by Ahedo et al [7], Ramos, Merino and Ahedo [8] , Lorzel, and Mikellides [9] and Domínguez-Vázquez et al [10] have also been reported. On the experimental side, Qin et al [11,12] have investigated, both in Hall type and Ion thrusters, unstable discharge phenomenon in which discharge voltage oscillations appear, particularly at high discharge currents or low flow rate conditions.…”
Section: Introductionmentioning
confidence: 99%